2020
DOI: 10.15451/ec2020-05-9.12-1-15
|View full text |Cite
|
Sign up to set email alerts
|

State of knowledge and conservation of the snake fauna of the “Brejos de Altitude” in the Pernambuco Endemism Center, Northeastern Brazil

Abstract: The Atlantic Forest is originally distributed along the Brazilian coast from the states of Rio Grande do Norte to Rio Grande do Sul, and it presents many different vegetal physiognomies. Brejos de Altitude is a set of relict altitudinal forests in northeastern Brazil with a distinct and poorly studied biota representing special areas within the Atlantic Forest. The snake fauna of these forests is still poorly understood despite the increasing amount of information available. The aim of this study was to furnis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
8
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(9 citation statements)
references
References 7 publications
1
8
0
Order By: Relevance
“…The biodiversity of the CMFEs has been the subject of several studies trying to infer the historical processes responsible for the formation of the unique organismic composition of these areas (e.g., Carnaval 2002;da Silva et al 2018;Castro et al 2018;Menezes et al 2020). In parallel, other studies have described the remarkable herpetological diversity (Pereira-Filho and Montingelli 2011;Mariano and Martins 2017;Freitas et al 2019a;Pereira-Filho et al 2020) and the hidden endemic diversity of these areas (e.g., Graboski et al 2015;Mângia et al 2018).…”
Section: Discussionmentioning
confidence: 80%
See 1 more Smart Citation
“…The biodiversity of the CMFEs has been the subject of several studies trying to infer the historical processes responsible for the formation of the unique organismic composition of these areas (e.g., Carnaval 2002;da Silva et al 2018;Castro et al 2018;Menezes et al 2020). In parallel, other studies have described the remarkable herpetological diversity (Pereira-Filho and Montingelli 2011;Mariano and Martins 2017;Freitas et al 2019a;Pereira-Filho et al 2020) and the hidden endemic diversity of these areas (e.g., Graboski et al 2015;Mângia et al 2018).…”
Section: Discussionmentioning
confidence: 80%
“…There are two general types of CMFEs distributed in Planalto da Borborema: those located in its eastern portion that present a more humid climate and those located in its western region that are characterized by drier and seasonal climates. Species of snakes closely related to BAF forms are frequently registered in eastern CMFEs, which frequently present records of BAF endemic species such as Echinanthera cephalomaculata Di Bernardo, 1994, Bothrops leucurus Wagler, 1824, and Lachesis muta (Linnaeus, 1766) (Freitas et al 2019b;Pereira-Filho et al 2020). On the other hand, western CMFEs are mainly influenced by the Caatinga dry forest and frequently present elements typical from this ecoregion, with records of Caatinga endemic species such as B. erythromelas, Thamnodynastes almae Ferreira, 2003, Thamnodynastes phoenix Franco, Trevine, Montingelli andZaher, 2017, and Thamnodynastes sertanejo Bailey, Thomas and da Silva, 2005(Rodal et al 2008Freitas et al 2019a;Pereira-Filho et al 2020).…”
Section: Discussionmentioning
confidence: 99%
“…nov. Including the species previously recorded for Brazilian Northeast region ( Santos et al 2022 ) and Pernambuco state ( França et al 2013 ; Souza et al 2013a , 2013b ; Souza and Santos 2017 ; Gomes and Calor 2019 ; Pereira-Filho et al 2020 ), 169 and 43 species have now been recorded from the Brazilian Northeast region and Pernambuco state, respectively. All species in this study, except Chimarra potiguar and Oxyethira tica , constitute new records from the Brejos de Altitude.…”
Section: Discussionmentioning
confidence: 99%
“…The subgenus H. (Feropsyche) has knowledge shortfalls of the species (Linnean shortfalls), since ~ 40% were described only in the 21 st century (e.g., Johanson 2003;Johanson and Malm 2006;Johanson and Holzenthal 2010;Rueda-Martín and Miranda 2015;Vilarino and Calor 2017;Dumas and Nessimian 2019), and many species to be described. Considering the significant reduction of vegetation in the Brazilian Northeast Atlantic Forest, the Brejos de Altitude constitute areas of high priority for conservation (SOS Mata Atlântica & INPE 2019;Pereira-Filho et al 2020). Here we present the first study of caddisfly fauna from a Brejo de Altitude with a commented checklist.…”
Section: Introductionmentioning
confidence: 99%
“…The clear formation of two groups in the lizard dendrogram ( Figure 10A) seems to reflect the phytophysiognomies of the localities: Group I with seasonal (dry) forests west of Planalto da Borborema, which, despite some of them having remnants of Atlantic Forest (montane forests), are inserted in the Caatinga biome and, thus, are strongly influenced by it; and Group II (in which RVS Matas do Siriji is inserted) with predominantly ombrophilous (humid) forests east of Planalto da Borborema, typical of Atlantic Forest, including other montane forests. Some studies involving plants (Santos et al 2007, Rodal & Sales 2008 and snakes (Pereira-Filho et al 2020) as models, have demonstrated the division of montane forests into "wet" and "dry", with Planalto da Borborema being indicated as responsible for the division.…”
Section: Discussionmentioning
confidence: 99%